Gejolak Fujoshi Dalam Media Sosial (Peran Media Twitter Dalam Pembentukan Identitas Kelompok Fujoshi) - Fitriana, Rossa; Darmawan, Diaz Restu; Efriani, Efriani; Apriadi, Deny Wahyu (Vocational College of Diponegoro University, 2021)
This study discusses the phenomenon of fujoshi, a popular culture from Japan. Fujoshi is a woman's passion for manga or comics genre boys love, where the manga tells the story of the love relationship between men. This research was conducted using a qualitative research method with a virtual ethnography method approach, where the researcher traced twitter accounts that were actively uploading about the manga boys love. This study tries to describe how the identity of fujoshi is formed which shows the manga boys love fondness on social media, especially in twitter. The result of this study is that fujoshi still be considered as an abnormality and also considered to violate the norms of the society. However, social media is able to provide space for free expression to show the identity of their preferences without getting any social sanctions. Social media also builds the fujoshi identity which was initially considered a deviation, has now been accepted and spawned more works and formed a community that has the same passion for manga boys love that is bigger than before.